1988
DOI: 10.1159/000171852
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Index and Left Ventricular Function Changes in Cirrhosis Measured by Radionuclide Angiocardiography

Abstract: Radionuclide angiocardiography (RNAC) was used to measure cardiac function in 134 patients with cirrhosis. In 14 patients, with a cardiac outputs range of 4–20 liters/min, RNAC correlated significantly (r = 0.82) with cardiac output as measured by thermodilution. Studies of reproducibility in 72 patients showed that 30 % of the patients had a cardiac index (CI) which varied by 5 % or less on repeated study, and in 80 % in of the patients the CI varied by 15 % or less: the variability was similar for all ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…4 Most cardiomyopathies have been observed in alcoholic cirrhosis but nonalcoholic cirrhosis may be also associated with latent cardiomyopathy. 4,25 In the present study, elevated cardiac troponin I concentrations were mainly observed in patients with alcoholic cirrhosis because only one patient had another cause of cirrhosis. Thus, asymptomatic alcoholic cardiomyopathy might play a role in the increased troponin I.…”
Section: Discussionmentioning
confidence: 49%
“…4 Most cardiomyopathies have been observed in alcoholic cirrhosis but nonalcoholic cirrhosis may be also associated with latent cardiomyopathy. 4,25 In the present study, elevated cardiac troponin I concentrations were mainly observed in patients with alcoholic cirrhosis because only one patient had another cause of cirrhosis. Thus, asymptomatic alcoholic cardiomyopathy might play a role in the increased troponin I.…”
Section: Discussionmentioning
confidence: 49%